(3GdJCOjH GdEOGQj (B:s (3OQGSI abgjI aj VhA CMcGe GdeMceI GdEOGQjI GdYdjG (B/s - (3Rjf GdOjf, HdGd Cejfs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2015)
(3jJfGhd cJGH (B((3GdJCOjH GdEOGQj(B) (3GdPj bGe HJCdjag HdGd Cejf Rjf GdOjf aj MhGdj (B(481) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCMcGe GdEOGQjI(B) (3eJVefG GdeMJhjGJ GdJGdjI (B: 1- (3GdeNGdaGJ GdJCOjHjI GdJj JSJhLH GdJCOjH GdEOGQj, (B2- (3JYQja GdeNGdaI GdEOGQjI hYfGUQgG, (B3- (3CfhGY GdeNGdaGJ GdEOGQjI GdJj JSJhLH GdJCOjH GdEOGQj, (B4- (3GdSdWGJ GdeNJUI HGdJCOjH GdEOGQj, (B5- (3cjajI JMOjO GdGNJUGU HGdJCOjH GdEOGQj, (B6- (3GdLRGA GdJCOjHj, (B7- (3eGgjI GdLRGA GdJCOjHj hWHjYJg, jJVef eQGLY HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B467-473.s
Keywords: (3eUQ(B.s -- (3GdeMceI GdEOGQjI GdYdjGs; (3GfVHGW GdYeds -- (3bhGfjf hJTQjYGJs -- (3eUQs